2012
DOI: 10.1017/s095457941100068x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of the mother–child relationship in high-risk dyads: Application of the Emotional Availability Scales in an intergenerational, longitudinal study

Abstract: The present research examined how family psychosocial risk may be associated with emotional availability (EA) across age and time in two longitudinal, intergenerational studies with high-risk, disadvantaged mother-child dyads. Study 1 examined dyads during preschool and middle childhood. Study 2 examined a different sample of dyads, tested intensively at five time points (6, 12, and 18 months; preschool; and school age). Across studies, maternal childhood histories of aggression and social withdrawal predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 41 publications
5
52
0
6
Order By: Relevance
“…Thirdly, due to the cross-sectional design of the study, conclusions about causality, and in particular about the direction of the mediational effect, have to be drawn carefully. Furthermore, other possible covariates that have shown relations to maternal EA, such as child temperament [53], social support [54], and maternal history of trauma [55], were not assessed in the present study. Another factor that might be interesting to investigate is the role of maternal intelligence, as it could be related to maternal ToM and might have a moderating role with regard to the prediction of maternal EA.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, due to the cross-sectional design of the study, conclusions about causality, and in particular about the direction of the mediational effect, have to be drawn carefully. Furthermore, other possible covariates that have shown relations to maternal EA, such as child temperament [53], social support [54], and maternal history of trauma [55], were not assessed in the present study. Another factor that might be interesting to investigate is the role of maternal intelligence, as it could be related to maternal ToM and might have a moderating role with regard to the prediction of maternal EA.…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study has shown an association between smoking during pregnancy and different psychiatric disorders in offspring [8]. In addition, some of the women probably have a history of maltreatment themselves and many have had conduct problems, which are likely to increase the risk of difficulties in a mother-child relationship and the child's behavioural problems [39,42,49]. In this study, more than a third of the parturients with a residential school history were single and many probably lack support from their own parents as well, which emphasizes the need of external social support.…”
Section: Discussionmentioning
confidence: 99%
“…Sebaliknya ibu dengan perilaku yang positif seperti menciptakan suasana yang menyenangkan, sikap yang hangat dan terbuka akan berpengaruh positif terhadap perkembangan anak. Kedekatan ibu anak ini pada akhirnya akan mempengaruhi pencapaian akademik anak diusia sekolah (Stack et al, 2012).…”
Section: Pengaruh Berat Badan Lahir Terhadap Perkembangan Anak Prasekunclassified